Istotny pogląd Prezesa UOKiK jako element postępowania sądowego - Gutkowski, Paweł (Studia Prawa Publicznego, 2018)
This article concerns the legal institution of observations submitted in civil proceedings by the President of the Office of Competition and Consumer Protection (hereinafter: President of the UOKiK). This institution is analysed within the framework of the hitherto practice of the Polish courts and the President of the UOKiK. Significant legal issues linked with the submission of the said observations and the way they are processed by the courts are presented, and premises for submitting these observations by the President of the UOKiK described. It is pointed out that submitting an observation is contingent upon the existence of public interest as well as occurrence of a significant question which is relevant to the case. Such a question needs to deal with the widely understood protection of competition and consumers. It is also noted that observations may only be submitted with regard to an actual case heard by the court. It may be addressed to either general, administrative or arbitration courts as well as to the Supreme Court. The article contains a description of the procedure of submitting observations, taking into account the settled practice of the President of the UOKiK. Within that scope issues concerning an application for submitting observations and formal requirements that such observations need to satisfy are also discussed. Furthermore, an attempt is made to determine the legal character of the said institution, taking into account the views presented in caselaw and literature. In that context a possibility of qualifying these observations as evidence has been excluded. Finally, the principles that need to be adopted by the courts when they examine the observations are discussed and the fact that courts have no competence to verify the observations submitted by the President of the UOKiK in respect of formal requirements and conditions for submission is stressed.